Income inequality processes in hungarian settlement area following the 2008 economic crisis - Egri, Zoltán (Studia Mundi – Economica, 2022)
The study aims to describe the income inequality processes at the settlement level in Hungary following the economic crisis that began in 2008-2009 and the period that affected the recovery. The analysis pays particular attention to territorial heterogeneity, which the author interprets along the lines of development categories (clubs) used in domestic territorial development, and assumes the significant differentiation of the income inequality processes of these clubs. According to the results, the different development clubs are significantly different both from the national average and from each other in terms of income growth, growth factors, inequality trajectories, and income dynamics.